High concentrations of methyl fluoride affect the bacterial community in a thermophilic methanogenic sludge. - Liping Hao; Fan Lü; Qing Wu; Liming Shao; Pinjing He (PLoS ONE, 2014)
To precisely control the application of methyl fluoride (CH3F) for analysis of methanogenic pathways, the influence of 0-10% CH3F on bacterial and archaeal communities in a thermophilic methanogenic sludge was investigated. The results suggested that CH3F acts specifically on acetoclastic methanogenesis. The inhibitory effect stabilized at an initial concentration of 3-5%, with around 90% of the total methanogenic activity being suppressed, and a characteristic of hydrogenotrophic pathway in isotope fractionation was demonstrated under this condition. However, extended exposure (12 days) to high concentrations of CH3F (>3%) altered the bacterial community structure significantly, resulting in increased diversity and decreased evenness, which can be related to acetate oxidation and CH3F degradation. Bacterial clone library analysis showed that syntrophic acetate oxidizing bacteria Thermacetogenium phaeum were highly enriched under the suppression of 10% CH3F. However, the methanogenic community did not change obviously. Thus, excessive usage of CH3F over the long term can change the composition of the bacterial community. Therefore, data from studies involving the use of CH3F as an acetoclast inhibitor should be interpreted with care. Conversely, CH3F has been suggested as a factor to stimulate the enrichment of syntrophic acetate oxidizing bacteria.